The Effectiveness of Homelessness and Beggars Handling Related to the Badung Regency Regulation Number 7 of 2016 Concerning Public Order and Peace of the Community - Ni Putu Yunika Sulistyawati; Sang Ayu Made Ary Kusumawardhani (Dwijendra University, 2020)
The flow of urbanization to Badung Regency and other cities as it gets bigger as the regional economy develops. On the other hand, the opportunities available and the opportunities to try in the city are not able to accommodate urbanization actors because of the limited skills that have in the home area so as to cause one of the problems is the onsling of homeless people and beggars. The formulation of the problem faced is the effectiveness of tackling homelessness and beggars related to the regulation of badung district number 7 in 2016 on public order and community peace, what is done by the badung district government in dealing with homelessness and beggars? The type of research that the author uses in this study is legal research with empirical aspects. Given the effectiveness of tackling homelessness and beggars related to the Badung regency regional regulation number 7 of 2016 concerning public order and public order. Researchers have conducted field research with interviews and observations in several areas of Badung, Jimbaran, Mengwi, Kapal, Nusa Dua districts and several places in Badung regency. The conclusion is that the factors causing the occurrence of vagrants and beggars. Internal factors include poverty, age, low levels of formal education, parental consent, low levels of skills, mental attitudes, while external factors include; hydrological conditions, agricultural conditions, conditions of infrastructure and physical facilities, access to information and business capital, primitive conditions of urban communities, weaknesses in handling vagabonds and beggars in cities. Based on the research results, the effectiveness of tackling homelessness and beggars related to the Badung regency regional regulation number 7 of 2016 concerning public order and public peace, especially in article 27 point 1 regarding each prohibited from carrying out vagrant and beggar activities, busking and trading hawkers on public vehicles, government offices, road junctions / traffic light, parks owned by local governments, schools, hospitals and health centers have been effective, proven to reduce numbers vagrants and beggars in Badung Regency, the efforts made by the Badung regency government in dealing with homeless people and beggars are by taking preventive measures to prevent homelessness and beggars before the occurrence or occurrence of homelessness and beggars and prevention of repressions including; about Secrets, temporary shelter and delegation.